(untitled) (Studia Prawnicze / The Legal Studies, 1982)
This study presents basic problems concerning the notion and criteria of con- tinual offence. We should state right away, that the issue is mentioned among the most controversial ones in the doctrine and in particular in the judicature of the Supreme Court, above all because the criminal code of 1932 contained no regulation of the institution. Binding criminal code of 1969 introduced a statutory notion of continual offence but gave neither the definition, nor pointed out criteria allowing to designate it. According to article 58 of the criminal code in case of convinction for a continual offence, the court may pronounce the penalty up to the limits of statutory maxi- mum of punishment increased by half, however, not exceeding the limits foreseen for a particular kind of penalty. In this study doctrinal concepts of continual offence commited by simple and multiple act were presented. The author is of the opinion that the whole contro- versy is apparent, since the notion of one continual offence is identical to that of one i(offensive) act of continual character; they both express particular legal con- cept according to which what fulfills particular criteria is considered one continual offence. For the definition of continual offence elements which constitute an offence or (offensive) continual act are decisive, i.e. whether the offence consists of several acts, and if so, of what acts (natural, offensive, violating criminal law provisions, or factual events, facts, elements or purposeful activities). In the doctrine and in Supreme Court judicature each of these notions was applied and each has its proponents; their opinions were critically analysed in this study. We present herewith the following interpretation of the notion of continual offence: by the latter we understand occurance of two or more acts violating pro- bisions of the criminal law, which are considered a continual offence in case defined criteria are met. If definition of the notion of continual offence is rather of theoretical chara- cter, definition of criteria of continual offence has above all practical meaning. It allows us to state, when particular acts violating criminal law provisions and staying in real concurrence, are to be considered a continual offence. In this study, basic directions of interpretation as to subjective and objective criteria of continual offence were presented in the light of doctrinal opinions and those of Supreme Court judicature. As concerns subjective criteria, existence of precedent intent to commit a continual offence was distinguished and discussed, and as concerns objective criteria, the following ones were presented: — identity of legal interest, or of legal classification; — identity of offence of the same kind; — homogeneity of the situation in which a perpetrator finds himself and which renders commiting offence possible; — homogeneity of method of commiting offence; — proximity in time and identity of place of commiting offence; — identity of the wronged person, in case the offence consists of attempt against strictly personal interest; — degree of social danger contained in the act.